2016
DOI: 10.1111/bcp.13147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bisphosphonate as an adjunct to nonsurgical periodontal therapy in the management of periodontal disease: a systematic review

Abstract: Keywords Bisphosphonates, scaling and root planning, periodontal disease, systematic review AIMSThe aim of this systematic review was to assess the efficacy of bisphosphonate therapy as an adjunct to scaling and root planing (SRP) in the management of periodontitis. METHODSDatabases (MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Cochrane Oral Health Group Trials Register databases) were searched up to and including July 2016. The primary outcome was probing depth (PD), and the secondary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 48 publications
0
40
0
2
Order By: Relevance
“…Treatment of periodontitis with adjuncts aims to facilitate manual debridement in reducing further disease progression. Studies have shown that SRP when performed with other existing adjunct therapies (such as bisphosphonates, statins, application of lasers and photodynamic therapy) is more effective in reducing periodontal inflammation in systemically healthy individuals compared with SRP alone. Similarly, locally delivered metformin should be used to compare the observed effects in periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of periodontitis with adjuncts aims to facilitate manual debridement in reducing further disease progression. Studies have shown that SRP when performed with other existing adjunct therapies (such as bisphosphonates, statins, application of lasers and photodynamic therapy) is more effective in reducing periodontal inflammation in systemically healthy individuals compared with SRP alone. Similarly, locally delivered metformin should be used to compare the observed effects in periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these difficulties, various adjunctive treatments have been investigated and proposed to supplement SRP. These include systemic and localized delivery of antibiotics, bisphosphonates, lasers and photodynamic therapy to reduce bacterial counts and improve clinical periodontal parameters such as probing depth reduction, gaining clinical attachment level and bone defect (BD) fill in periodontitis . Among these compounds, locally delivered metformin have recently been introduced for the treatment of periodontal bone defects in chronic periodontitis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the existence of serious side effects to these drugs, such as MRONJ, requires for said risks to be carefully compared in a risk-benefit perspective. 17 The presented hypothesis is that there may be a relationship between PD and MRONJ. To the best of our knowledge, no previous systematic approach has been used to study the relationship between PD and MRONJ.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, these reports challenge the concept that bisphosphonates have a negative effect in PD, representing an interesting avenue for its potential use as adjuvants or host modulation therapies for PD. Nonetheless, the existence of serious side effects to these drugs, such as MRONJ, requires for said risks to be carefully compared in a risk‐benefit perspective …”
Section: Introductionmentioning
confidence: 99%